2007
DOI: 10.1159/000107957
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Tube® (Promedon) Malleable Penile Implant

Abstract: Introduction: The main advantages of semirigid penile prosthesis are simple implantation, ease of use, very low risk of mechanical failure and more financial suitability for patients in developing countries. Aim: To evaluate reliability and safety of Tube® (Promedon, Cordoba, Argentina) penile prosthesis in the surgical treatment of erectile dysfunction. Patients and Methods: This retrospective case series was conducted on 83 patients who underwent Tube penile implant surgeries between 2001 and 2006. The choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the present study, inter-corporeal septal perforation occurred in 2.3% and small glanular urethral injury in 1.5% of patients due to difficult expansion caused by cavernosal tissue fibrosis and early experience with penile implant surgery. Whereas, Fathy et al [8] reported urethral injury and corporeal perforation in 0% in their series and Song et al [20] reported corporeal perforation in three of 224 patients in their series.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study, inter-corporeal septal perforation occurred in 2.3% and small glanular urethral injury in 1.5% of patients due to difficult expansion caused by cavernosal tissue fibrosis and early experience with penile implant surgery. Whereas, Fathy et al [8] reported urethral injury and corporeal perforation in 0% in their series and Song et al [20] reported corporeal perforation in three of 224 patients in their series.…”
Section: Discussionmentioning
confidence: 92%
“…Although, their reliability has improved in the last decade, their complications are still present [7]. The ease of use, simplicity of implantation, the rarity of mechanical failure, and cost-effectiveness make malleable penile prostheses more convenient for our patients [8]. The present study aimed to evaluate the surgical outcome, complications, and patients, satisfaction with Tube® malleable penile prosthesis (Promedon, Cordoba, Argentina) in diabetic and non-diabetic patients with refractory ED.…”
Section: Introductionmentioning
confidence: 98%
“…In Egypt the semi-rigid implant is commonly used in management of erectile dysfunction not only for its technical facility to be applied and less incidence of mechanical failure but also due to low cost [5]. To our knowledge, most surgeons prefer the Penoscrotal approach during application of malleable implant but infrapubic approach were preferred for inflatable prosthesis [7].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to low cost, easy application, easy use and less incidence of mechanical complications. The drawbacks of semi-rigid penile implants include permanent erections, inability to mask it and liability for prolonged pain and erosion [5]. There are no available studies to compare infrapubic approach with various approaches for semi-rigid penile implant.…”
Section: Introductionmentioning
confidence: 99%
“…Currently 48 This device permits malleability up to a 1301 angle. The proximal segments are trimmable every 5 mm and there are both 10 and 15 mm rear tips.…”
Section: Presentmentioning
confidence: 99%